2001
DOI: 10.1046/j.1460-9568.2001.01421.x
|View full text |Cite
|
Sign up to set email alerts
|

Subunits of the nitric oxide receptor, soluble guanylyl cyclase, expressed in rat brain

Abstract: Despite the widespread use of nitric oxide as a signalling molecule in the central nervous system, the molecular makeup of its receptor, soluble guanylyl cyclase (sGC), therein is poorly understood. Accordingly, RT-PCR and in situ hybridization were used to identify sGC subunits expressed in rat brain. In addition to the expected mRNA for alpha 1 and beta1 subunits, message for the beta 2 subunit was detected in the cerebellum at all developmental stages investigated (1--150 days postnatum). The use of degener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
56
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 29 publications
15
56
4
Order By: Relevance
“…The two functionally relevant subunit compositions in the hippocampus are ␣ 1 ␤ 1 and ␣ 2 ␤ 1 . The distribution of NOsGC ␤ 1 subunit and its mRNA has been reported previously (Gibb and Garthwaite, 2001;Burette et al, 2002;Ding et al, 2004;Pifarre et al, 2007), and it was shown to be localized in pyramidal cells and in some interneurons. In addition, ␣ and ␤ subunits were found to colocalize in the same cells (Ding et al, 2004), but the ␣ 1 -and ␣ 2 -containing complexes were not distinguished.…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…The two functionally relevant subunit compositions in the hippocampus are ␣ 1 ␤ 1 and ␣ 2 ␤ 1 . The distribution of NOsGC ␤ 1 subunit and its mRNA has been reported previously (Gibb and Garthwaite, 2001;Burette et al, 2002;Ding et al, 2004;Pifarre et al, 2007), and it was shown to be localized in pyramidal cells and in some interneurons. In addition, ␣ and ␤ subunits were found to colocalize in the same cells (Ding et al, 2004), but the ␣ 1 -and ␣ 2 -containing complexes were not distinguished.…”
Section: Introductionsupporting
confidence: 57%
“…Cell type-specific expression of NOsGC subunits and its association with nNOS Expression of the NOsGC subunit mRNA has been reported previously in 8-d-old rat hippocampus at low magnification, showing a weak ␣ 1 and a stronger ␣ 2 and ␤ 1 subunit expression (Gibb and Garthwaite, 2001). In adult rats, a large difference appears to be maintained between the ␣ 1 and ␣ 2 subunit expression at low magnification (Pifarre et al, 2007, their Fig.…”
Section: Synapse-specific No Production In Gabaergic Synapsesmentioning
confidence: 61%
See 1 more Smart Citation
“…Weak β1 expression has been described in the embryo, which increases after birth to be widely expressed in the adult (Giuili et al, 1994). The level of α2 mRNA expression in adult animals appears to be less than in 8-day-old animals, labelling being concentrated in the granule cell layer (Gibb and Garthwaite, 2001).…”
Section: Discussionmentioning
confidence: 97%
“…The enzyme soluble guanylyl cyclase (sGC) has often been referred to as the "NO receptor", because of its central role in binding NO and relaying the NO signal [6]. The soluble isoforms of sGC are activated by NO, which is the product of the enzyme action of NO synthase (NOS) on L-arginine, leading to the formation and elevation of intracellular levels of the second messenger molecule, cGMP.…”
Section: No Signaling In the Cnsmentioning
confidence: 99%